Pengaruh Strategi Promosi dan Pelayanan Terhadap Keputusan Pembelian Air Minum Isi Ulang - Reti Prisilia; Suci Mahabbati (Journal Islamic Economic and Bussines Studies, 2022)
This research is motivated by a phenomenon that is a promotional strategy carried out by coupons where if the next 7 coupons are free, if 100 coupons are free glasses, while 200 coupons are free 1 gallon, but the sale of drinking water at this depot cannot be widely reached, namely consumers are still around the village where the Alga Water drinking water depot is in Koto Baru Semerap. Many consumers feel disappointed with the services provided in purchasing Alga Water Refillable Drinking Water at Koto Baru Semerap because the owners or employees are not friendly in serving consumers. So it is not uncommon for consumers to feel annoyed with the unfriendliness. This research is a type of quantitative research. Quantitative analysis in this study is needed to provide an overview of the research results. This study aims to find an explanation of the measurement of the influence of promotion and service strategies on purchasing decisions for drinking water refilled with algae water in Koto Baru Semerap. From the results of the study, it shows that the influence of promotion and service strategies on purchasing decisions for drinking water refilled with algae water in Koto Baru Semerap from the ANOVA test or F test turns out to be 20,913 based on the above calculations, it can be decided as follows: where fcount > ftable, namely 20.913 > 3.34 and 0.000 <0.05, then Ha is accepted and Ho is rejected, which means that Promotion and Service Strategy together have a significant effect on Purchase Decisions. Based on the output, it is shown that the determinant value of Adjusted R is known to be the magnitude of the influence of Promotion Strategy (X1) and Service (X2) together on Consumer Purchase Decisions (Y) can be seen from the value of R^2 value of 0.608 if it is presented as 60.8%.